Do weather factors lead to partial brood losses in the Marsh Harrier Circus aeruginosus?. Issue 2 (4th March 2017) - Kryński, Kamil; Goławski, Artur; Kasprzykowski, Zbigniew
Abstract : Numerous studies have shown that local climatic conditions influence reproduction in birds. Although the effect of weather on brood success has often been tested, its influence on brood reduction has generally been overlooked. Such losses are common in raptors, because asynchronous hatching and the consequent age differences between nestlings govern their subsequent fate. The effects of weather and selected breeding parameters (hatching dates, numbers of nestlings in broods, pair density) on brood losses in the Marsh Harrier were studied in four fishpond complexes in east-central Poland in 2007–2009 and in 2011. Partial losses were dependent on the size of the brood and increased with the number of nestlings. The weather had no effect on brood reduction. Local weather conditions seem not to affect brood reduction, which would rather be related to other factors, such as for instance the number of hatched nestlings.